2010
DOI: 10.1644/09-mamm-a-134r.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fluctuating asymmetry of white-tailed deer antlers in a three-dimensional context

Abstract: Fluctuating asymmetry, random departure from perfect symmetry in bilateral traits, has been proposed as an indirect indicator of individual quality. Sexually selected traits, such as deer antlers, are hypothesized to demonstrate decreasing level of fluctuating asymmetry with increasing trait size and decreasing level of fluctuating asymmetry with increasing age. These hypotheses have been previously tested for antlers using linear measurements to quantify fluctuating asymmetry. However, antlers are complex, 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…Thus, high-quality individuals are predicted to produce large, highly symmetric structures that confer greater competitive success during intraspecific encounters, whilst also providing females with a reliable cue of the bearer's genetic quality [65]. Our results show that as males aged there was a corresponding increase in the amount of absolute FA expressed-a finding that is consistent with some studies (e.g., [25,66]), but not others (e.g., [26,54]). We note that other studies that have employed a relative measure of asymmetry have shown a negative relationship between FA and age (e.g., [67,68]).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, high-quality individuals are predicted to produce large, highly symmetric structures that confer greater competitive success during intraspecific encounters, whilst also providing females with a reliable cue of the bearer's genetic quality [65]. Our results show that as males aged there was a corresponding increase in the amount of absolute FA expressed-a finding that is consistent with some studies (e.g., [25,66]), but not others (e.g., [26,54]). We note that other studies that have employed a relative measure of asymmetry have shown a negative relationship between FA and age (e.g., [67,68]).…”
Section: Discussionsupporting
confidence: 90%
“…Following Palmer (1994 [53]), a two-way ANOVA showed that between sides variation was significantly greater than the measurement error for all traits (coronet circumference: me% = 4.73; F (9,60) = 39.8, p < 0.001; brow tine length: me% = 12.9; F (9,60) = 493.8, p < 0.001; beam circumference: me% = 6.71; F (9,60) = 40.14, p < 0.001; antler length: me% = 5.17; F (9,60) = 503.8, p < 0.001). There was an average measurement error across the four traits of 7.4%, broadly comparable with studies employing advanced photogrammetric methods to measure antler traits (e.g., [54,55]). We then tested for directional asymmetry using paired t-tests and results indicated that three measurements taken showed FA (brow tine length: t = −0.78, p = 0.44; beam circumference: t = −1.27, p = 0.44; curved antler length: t = 1.38, p = 0.17), and one measurement, coronet circumference, showed directional asymmetry (t = 2.48, p = 0.02; mean right/left = 184.8 mm/183.2 mm).…”
Section: Antler Collection and Measurementsupporting
confidence: 67%
“…Many centrosaurines exhibit asymmetry from side to side in epiparietal number and morphology, similar to the differences in cervids ( Ditchkoff & deFreese, 2010 ) and specifically caribou ( Miller, 1986 ). The extreme asymmetry is ep1 and ep2 in Lokiceratops is unusually pronounced when compared to other centrosaurines such as Coronoceratops brinkmani , Centrosaurus, Styracosaurus albertensis , Einiosaurus procurvicornis , and Pachyrhinosaurus lakustai .…”
Section: Description and Comparative Anatomymentioning
confidence: 67%
“…As, according to our results, size was unrelated to symmetry, it could be expected that the cost of larger ornamentation would create developmental stress for their owners, heavier individuals not being the only ones capable of bearing the handicap of growing large traits or symmetries. If sexual characters, like antlers, are costly to produce (Ditchkoff & deFreese, 2010) the relative cost to produce equal-sized traits would be the same for lighter weight individuals. This might not be the case in wild animals, but can be explained in this research by the fact that the studied animals are bred in an artificial environment, so those costs may be perfectly covered.…”
Section: Discussionmentioning
confidence: 99%